2003
DOI: 10.1677/joe.0.1770147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular studies of identification of genes for osteoporosis: the 2002 update

Abstract: We aim to give a comprehensive review, updated to 2002, of the most important and representative molecular genetic studies, performed mainly within the past decade, that aimed to identify the gene(s) involved in osteoporosis. Early reviews were largely confined to association studies in humans, but we review here, separately, the results of both association and linkage studies in humans, and quantitative trait locus (QTL) mapping in animal models. The main results of all the studies are tabulated for compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
168
1
9

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(182 citation statements)
references
References 315 publications
4
168
1
9
Order By: Relevance
“…Marker D2S405 in the same region on 2p23 was reported to be linked to forearm BMD by Niu et al 23 Other regions where we observed interesting lod-scores coincide with regions reported in other studies and/or known to contain candidate genes for bone-related traits. 5,12 A formal meta-analysis will help elucidate whether these findings may in fact indicate the existence of genomic regions containing susceptibility genes for osteoporosis shared across different populations. In particular, chromosome 5q33 yielded lod-scores of more than 1 in both univariate analysis for FN BMD and LS BMD and bivariate analysis for FN/LS BMD and FN/TR BMD in our pedigrees, and coincides with the region reported by Koller et al 24 for FN BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Marker D2S405 in the same region on 2p23 was reported to be linked to forearm BMD by Niu et al 23 Other regions where we observed interesting lod-scores coincide with regions reported in other studies and/or known to contain candidate genes for bone-related traits. 5,12 A formal meta-analysis will help elucidate whether these findings may in fact indicate the existence of genomic regions containing susceptibility genes for osteoporosis shared across different populations. In particular, chromosome 5q33 yielded lod-scores of more than 1 in both univariate analysis for FN BMD and LS BMD and bivariate analysis for FN/LS BMD and FN/TR BMD in our pedigrees, and coincides with the region reported by Koller et al 24 for FN BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Like many other common diseases, multiple factors, including genetic variations, determine predisposition for onset or progression of osteoporosis, as has been indicated by genetic-epidemiological studies (Peacock et al 2002;Albagha and Ralston 2003). Numerous studies on genetic risks for osteoporosis have been investigated to date, mainly by association studies and linkage analysis for quantitative trait BMD (Liu et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…20 In agreement with this theory, many studies showed the association between the Sp1 polymorphism and the risk for osteoporosis or fractures. 5 Although inconsistent association results exist, two meta-analyses 21,22 supported that the presence of the s allele was significantly associated with low BMD and fracture prevalence though such effect on bone metabolism was moderate and could be easily modified by environmental factors. In keeping with this, one pharmacogenetic research demonstrated that the s allele negatively influences BMD response to the etidronate therapy since femoral neck BMD obviously increased in the SS group while decreased in the Ss/ss group.…”
mentioning
confidence: 99%
“…23 In the osteoporosis research field, although few haplotype analyses were done in the pharmacogenetic context, some haplotypes of certain candidate genes were already studied and associated with bone phenotypes. 5 Moreover, the underway 'HapMap' project 24 holds promise for the genome-wide association studies that will use haplotype blocks to unravel some mystery of osteoporosis and provide an ideal regimen of treatment for osteoporotic patients according to the complete genetic evaluations. Yet, a large number of SNPs will be required for such whole genome association studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation